2021
DOI: 10.3390/ijms22052406
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography of Titanium Affects Their Osteogenic Potential through DNA Methylation

Abstract: It is widely accepted that sandblasted/large-grit/acid-etched (SLA) surfaces of titanium (Ti) have a higher osteogenic potential than machined ones. However, most studies focused on differential gene expression without elucidating the underlying mechanism for this difference. The aim of this study was to evaluate how the surface roughness of dental Ti implants affects their osteogenic potential. Mouse preosteoblast MC3T3-E1 cells were seeded on machined and SLA Ti discs. The cellular activities of the discs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…HA is like a bioceramic that has very good biological properties facilitating bone repair and reconstruction [40]. The surface roughness of titanium alloys suitable for the growth of osteoblasts is 0.2-0.7 µm, and, in the literature, many reports can be found on the protective and bioactive layers on titanium alloys and their corrosion resistance [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…HA is like a bioceramic that has very good biological properties facilitating bone repair and reconstruction [40]. The surface roughness of titanium alloys suitable for the growth of osteoblasts is 0.2-0.7 µm, and, in the literature, many reports can be found on the protective and bioactive layers on titanium alloys and their corrosion resistance [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…87 Treatment with 5-aza-2′-deoxycytidine of osteoblasts grown on titanium discs of two different surface characteristics decreased DNA methylation on both surfaces and induced gene expression of alkaline phosphatase. 88 Decitabine (5-aza-2′-deoxycytidine) was found to reduce bone loss in a mouse periodontitis model by inhibiting osteoclastogenesis. 89 Another challenge in periodontal tissue regeneration is reducing inflammation.…”
Section: Epi-drugsmentioning
confidence: 99%
“…29 In addition, the methylation level of the alkaline phosphatase gene was lower in osteoblast cells grown on smooth titanium surfaces than in cells grown on modified titanium surfaces. 88 Interestingly, surface decontamination using mechanical methods was found to further influence epigenetic markers. 111 In a previous study, preosteoblastic cells were grown on titanium discs with various surfaces: machined, dual acid-etched, and acid-etched nanohydroxyapatite-blasted.…”
Section: Modifying Surface Structure To Improve Implant-bone Interact...mentioning
confidence: 99%
“…In this regard, some studies on implant surfaces and osteoblast differentiation have focused on differences in the osteogenic potential of surfaces as a function of gene expression levels, and some have reported that implant surface topography can alter cellular activity (Zheng et al, 2020;Ichioka et al, 2021). A study by Cho et al concluded that the surface topography of Ti implants affects their osteogenic potential through epigenetic changes, raising the possibility of using epidrugs to enhance osteogenesis on implant surfaces (Cho et al, 2021).…”
Section: Dna Methylationmentioning
confidence: 99%